A dragon's guide to the care and feeding of humans - Yep, Laurence, 1948-; Ryder, Joanne (Yearling, 2016)
The dragon lady Miss Drake is shocked when her new human pet, precocious Winnie, seems to believe that she--the dragon--is her pet. Miss Drake sets about showing Winnie that things are really the other way around--but then Winnie's sketches of San Francisco's fantastic, mysterious creatures come to life and escape into the city's streets.